A note on the tail behavior of randomly weighted and stopped dependent sums - Dindienė, Lina; Leipus, Remigijus (Nonlinear Analysis: Modelling and Control, 2015)
In this paper, we deal with the tail behavior of the maximum of randomly weighted and stopped sums. We assume that primary random variables (with a certain dependence structure) are identically distributed with heavy-tailed distribution function and random weights are nonnegative. In this note, we specify some conditions for the (weak) asymptotics of the tail of random maximum.
Keywords: heavy tails; extended negative dependence; asymptotic tail probability